ANALYSIS OF AUDIT QUALITY DIFFERENCES, MANAGERIAL OWNERSHIP, FINANCIAL STABILITY, AND CAPITAL TURN OVER ON FRAUD AND NON-FRAUD COMPANY - Rakendro Wijayanto (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2015)
The purpose of this research ic to analyze audit quality differences, managerial ownership, financial stability and capital turnover on fraud and non fraud company. Population of this research are manufacturing company listed in Indonesian Stock Exchange (ISE) in year 2012 — 2014. Total sample of this research is 254 manufacturing company. Mann —Whitney test is used as the analysis method. The result of this research shows that audit quality and managerial ownership variables has significant differences between fraud and non fraud company. Whereas financial stability and capital return variables does not show any difference between fraud and non fraud company.